Translation, extension, and evaluation of usability, usefulness, and safety of a fall prevention and management program for people living with spinal cord injury and multiple sclerosis who use wheelchairs or scooters full time - Rice, Laura A.; Yehya, Malaak; Yi, Jennifer; Koziel, Stephen; Peterson, Elizabeth W. (Frontiers in Rehabilitation Sciences, 2024)
BackgroundFalls are prevalent among people living with Multiple Sclerosis (PwMS) and Spinal Cord Injury (PwSCI) who use wheelchairs or scooters (WC/S) full time, however, there is a scarcity of evidence-based fall prevention and management programs.ObjectiveTo describe the systematic translation of an in-person fall prevention and management program (Individualized Reduction Of FaLLs – iROLL) for PwMS to an online platform, extending its scope to include PwSCI, and to evaluate the preliminary useability, usefulness, and safety of the intervention.MethodsiROLL was systematically translated to an online platform (iROLL-O). PwMS and PwSCI who use a WC/S full time, experienced at least one fall within the past 36 months, and could transfer independently or with minimal to moderate assistance, enrolled in iROLL-O. Usability, usefulness, and safety were evaluated through 1:1 semi-structured interviews, gathering feedback on: perceived impact of the intervention on falls and functional mobility, program experiences, adverse events, and recommendations for improvement.ResultsFive participants successfully completed the iROLL-O program. No safety concerns were raised by participants. Themes emerging from the semi-structured interviews included: (1) barriers and facilitators to program access, (2) motivation for participation, (3) program outcomes, and (4) program content and structure. Participants reported reduced concerns about falling, enhanced functional mobility skills, and highlighted the supportive nature of synchronous group meetings for learning.ConclusionNo adverse events occurred during the implementation of iROLL-O and participants found the program to be useable and useful. Further testing is needed to examine efficacy among a large and diverse population.